Translocation (6;15)(q12;q15): A Novel Mutation in a Patient with Therapy-Related Myelodysplastic Syndrome - Ali, Saba F.; Sonu, Rebecca J.; Dwyre, Denis M.; Jonas, Brian A.; Rashidi, Hooman H. (Case Reports in Hematology, 2015)
Most myelodysplastic syndromes (MDS) present with loss or gain of chromosomal material and less commonly show translocations as a sole abnormality. In addition, certain translocations are more commonly seen in MDS than others, but to our knowledge, the presence of t(6;15) has not been reported in MDS, specifically therapy-related MDS (t-MDS) cases. Patients with t-MDS, a group of heterogeneous stem cell related disorders resulting as a latent complication of cytotoxic and/or radiation therapy, generally tend to have a poorer prognosis than de novo MDS. We present a unique case of a patient who initially presented with acute myeloid leukemia (AML) with a normal karyotype and FLT3-ITD and NPM1 mutations. The patient was successfully treated with chemotherapy and an autologous bone marrow transplant but subsequently developed a new FLT3-ITD negative t-MDS with a unique translocation, t(6;15)(q12;q15), three years after transplant. To our knowledge, this unique sole translocation has never been reported in MDS or t-MDS and given her successful response to treatment and remission, presence of this translocation may have some prognostic value.